Population Structure of Curraleiro Pé-Duro Cattle and its Relationship With the Serological Profile Against Pathogens of Economic and Zoonotic Interest - Freitas, Thais Miranda Silva; Dias, Juliana Moraes; Veríssimo, Ana Carolina Ferreira; Lobo, Joyce Rodrigues; Costa, Gustavo Lage; Moura, Maria Ivete de; Landi, Vincenzo; Martínez, Amparo Martínez; Carmo, Adriana Santana do; Fioravanti, Maria Clorinda Soares (Frontiers in Genetics, 2022)
Curraleiro Pé-Duro (CPD) cattle, a Brazilian local breed, are animals that are highly resistant to infectious and parasitic diseases. Strategies for the conservation of the breed and the genetic resistance to diseases should also consider the characteristics of the breed. The objective of this study was to analyze the diversity and population structure of the CPD breed using microsatellite markers and to correlate the serological profiles for causative agents of brucellosis, leptospirosis, neosporosis, leukosis, infectious bovine rhinotracheitis, and bovine viral diarrhea. DNA samples of 608 bovines were amplified and genotyped using 28 microsatellite markers for breed characterization. The genotypes were assigned to three clusters, indicating a substructure population related to the geographic distance. The observed heterozygosity was lower than that expected in most loci, and fixation index in the subpopulation values ranged from 0.03073 (ETH3) to 0.402 (INRA63) on cluster 1, from −0.02799 (INRA32) to 0.39359 (INRA63) on cluster 2, and from −0.06055 (INRA32) to 0.28483 (TGLA53) on cluster 3. The Brucella spp., Neospora caninum, and Bovine Leukemia Virus frequencies were significantly different (p<0.05) between clusters. The differences between the occurrences of diseases were not sufficient to indicate a genetic subpopulation with increased resistance to infections.